An Isolable Bis(Silanone–Borane) Adduct - Luecke, Marcel‐Philip (Chemistry, 2020)
The reaction of bis(silylenyl)‐substituted ferrocene 1 with two molar equivalents of BPh(3) yields the corresponding bis(silylene–borane) Lewis adduct 2. The latter is capable to activate CO(2) to furnish the borane‐stabilized bis(silanone) 3 through mono‐oxygenation of the dative Si(II)→B silicon centers under release of CO. Removal of BPh(3) from 3 with PMe(3) affords the corresponding 1,3,2,4‐cyclodisiloxane and the Me(3)P−BPh(3) adduct. All isolated new compounds were characterized and their molecular structures were determined by single‐crystal X‐ray diffraction analyses.